2004
DOI: 10.3928/01484834-20040701-07
|View full text |Cite
|
Sign up to set email alerts
|

Does Mindfulness Decrease Stress and Foster Empathy Among Nursing Students?

Abstract: This pilot study of baccalaureate nursing students explored the effects of an 8-week mindfulness-based stress reduction (MBSR) course on stress and empathy. The course was intended to provide students with tools to cope with personal and professional stress and to foster empathy through intrapersonal knowing. A convenience sample of 16 students participated in the course, used guided meditation audiotapes at home, and completed journal assignments. Stress and empathy were measured using paired sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
233
1
17

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(258 citation statements)
references
References 37 publications
7
233
1
17
Order By: Relevance
“…Eleven of the 29 studies cited were designed to evaluate such a programme (Table 3). Of these, six considered university-based education (Daniels et al 1988, Reynolds & Presly 1988, Nardi 1990, Wilt et al 1995, Cutcliffe & Cassedy 1999, Beddoe & Murphy 2004, four focused on hospital-based training (La Monica et al 1987, Yates et al 1998, Oz 2001, Ancel 2006, and one (Palsson et al 1996) studied community-based training.…”
Section: Empathy Evaluation Studiesmentioning
confidence: 99%
“…Eleven of the 29 studies cited were designed to evaluate such a programme (Table 3). Of these, six considered university-based education (Daniels et al 1988, Reynolds & Presly 1988, Nardi 1990, Wilt et al 1995, Cutcliffe & Cassedy 1999, Beddoe & Murphy 2004, four focused on hospital-based training (La Monica et al 1987, Yates et al 1998, Oz 2001, Ancel 2006, and one (Palsson et al 1996) studied community-based training.…”
Section: Empathy Evaluation Studiesmentioning
confidence: 99%
“…[1][2][3] Evidences indicate that most of the human successes are created in stressful conditions, but prolonged or high stress would lead to negative consequences, including mental and physical illnesses, sleep disorders, restlessness, irritability, forgetfulness, abnormal fatigue, reduced individual's resistance and recurrent infections, headaches, poor concentration, memory impairment, and reduced problem solving ability. 4,5 Likewise, prolonged or high stress levels in nursing students might affect memory, concentration, problem solving ability as well as might lead to decreased learning, coping, academic performance, depression, headache, attrition and serious health problems. [6][7][8] In mainland China, undergraduate nursing students spend full time practice in hospital in their final college year.…”
Section: Introductionmentioning
confidence: 99%
“…High stress and anxiety can impede concentration, memory and problem-solving ability, and so negatively affect task performance. 5 Furthermore, according to psychoneuroimmunology, when individuals experience stress, it is often accompanied by neuroendocrine responsivity and altered body's immune system. Studies focusing on psychological stress have suggested that both laboratory-induced acute stress, such as mental arithmetic or public speaking tasks, and kinds of life events all can induce some shifts in numbers of immune parameters.…”
Section: Introductionmentioning
confidence: 99%